Perancangan Tempat Sampah Cerdas Berbasis Arduino Uno di MTS Sunan Kalijaga - -, Nur Rokhman; Sumaryanto; Puteri Anindya Maulan (Jurnal Ilmiah Sistem Informasi, 2025)
The increasingly rapid development of technology has spread to every aspect of life, making people have to be technologically literate. At MTS Sunan Kalijaga Bawang, students carry out activities to gain knowledge and other activities. The students' parents provide them with food, drinks or money to shop in the school canteen. However, problems arise when eating and drinking are done outside the canteen zone. Observation results show that some students who eat and drink during breaks still throw away rubbish not in the places provided. The reason is that they are afraid that their hands will get dirty when opening the lid of the trash can, so they are reluctant to throw the trash where it is intended, resulting in the trash being scattered around. To overcome this problem, this research focuses on designing smart trash cans that can attract the interest of the public and MTS Sunan Kalijaga Bawang students to throw trash in the right place. This project uses the Arduino Uno platform to simplify and increase environmental awareness. Thus, the aim of this research is to create a more efficient and environmentally friendly waste processing system in schools.